Growth Analysis of Wheat in The Semiarid Climate at KURUKSHETRA, HARYANA - Narwal, R P (Annals of Arid Zone, 2016)
Growth analysis of what grown in Kurukshetra in a Semi-arid climate has been presented. Weekly observations on dry weight of leaves, stem, roots, total leaf area, specific leaf area ratio and pigment concentration are recorded. R.C.R. and U.L.R. are also calculated. The observations indicated that growth in whet is conditioned primarily by the pigment concentration in the leaves.